PENGOLAHAN DAN STRATEGI PEMASARAN PRODUK OLAHAN BURUNG PUYUH SEBAGAI ALTERNATIF PENINGKATAN INCOME SELAMA MASA PANDEMI COVID-19 DI KOTA KENDARI - Rusli Badaruddin; La Ode Arsad Sani; Natsir Sandiah; Syamsuddin Syamsuddin; Rahim Aka; Hairil A. Hadini; Fuji Astuty Auza; Amiluddin Indi (Jurnal Pengabdian NUSANTARA, 2021)
Kendari City as the provincial capital has the highest incidence of positive covid-19 cases compared to other districts / cities in Southeast Sulawesi, Until April 23, 2020 there were 17 positive patients with Covid-19 who were undergoing treatment. This has implications for decreasing consumption and people's income because they cannot carry out normal activities. The steps taken by the central and local governments to combat the Covid-19 pandemic are by carrying out social distancing or social restrictions by limiting distances between individuals and avoiding crowds. Another government policy is the implementation of work from home (WFH) or activities from home for some employees and school children. This condition adversely affects the economy of Kendari city. One of the solutions offered is raising quail by utilizing the house yard. Quail maintenance is quite easy, does not require a large area and the maintenance system can be completed in a minimalist manner. Quail products consist of eggs and meat. Quail meat is processed into rica-rica quail meat and eggs are processed into quail egg nest tofu. KKN-THEMATIC aims to provide insights and knowledge about processing and marketing of processed quail products to the public. The method used is a persuasive participatory method with direct extension activities and practices. The results that have been achieved in this KKN-TEMATIK activity are an increase in the knowledge and understanding of breeders and the community in developing their business sustainability by making processed quail products, aswell as marketing management of processed quail products.